Formative & Reflective Measurement Models - Neha Sharma; N.P Singh (Southeast Asian Business Review, 2025)
This research paper explores the distinctions between reflective and formative measurement models. The two commonly used methodologies in social science research for measuring latent variables. Reflective models believe that a latent variable causes its indicators, whereas formative models see the indicators contributing to the latent variable. The research paper explores each model's theoretical foundation focusing on their applicability in research domains such as marketing, psychology, and organizational behavior. In addition, the research paper analyzes these two models help in defining relationships in observable variable & latent variable such a nature of construct, causality & type of indicators. The research paper also focuses on the statistical approaches used to evaluate both models, including factor analysis, structural equation modeling, and path analysis etc. The Research paper will help researchers in identifying measurement models to improve the insights in identifying the model relationship among measurable & latent variable, and way to define construct validity and related phenomena.